AB0279 A Dynamic of the Multi-Biomarker Disease Activity Score in Methotrexate Incomplete Responders is Predictive for Clinical Response to Non-Biological or Biological Therapy in Early RA. (9th June 2015) - Hambardzumyan, K.; Bolce, R.J.; Saevarsdottir, S.; Forslind, K.; Karlsson, J.A.; Sasso, E.H.; Chernoff, D.; Hwang, C.C.; van Vollenhoven, R.F.
Abstract : Background: In our previous study (1) from the Swedish Farmacotherapy (SWEFOT) trial (2), we showed that a change of multi-biomarker disease activity (ΔMBDA) score (3) in methotrexate incomplete responders (MTX-IR) was predictive for subsequent response to non-biological triple therapy (TT; a combination of MTX with sulfasalazine and hydroxychloroquine) or to anti-tumour necrosis factor (anti-TNF) therapy. Objectives: To evaluate further how ΔMBDA score could be used to predict optimal choice of second-line treatment, by investigating different cut-offs and by comparing this to using the C-reactive protein (CRP) for prediction. Methods: 157 MTX-IR patients from the SWEFOT trial with complete data were grouped into those with and without big ΔMBDA (big decrease >22 and non-big decrease ≤22 respectively from baseline to Month 3) based on highest quartile. The change of CRP (ΔCRP) was studied in parallel using a cut-off based on the highest quartile (>28 & ≤28). Analysis was done by last observation carried forward. The proportion of clinical responders (DAS28 ≤3.2) across ΔMBDA groups between the two therapy arms was assessed by Breslow-Day test. Results: Among patients with ΔMBDA>22, 76% responded to TT and 47% to anti-TNF, while among the others more responded to anti-TNF (55% vs 38%; cross-comparison for all 4 groups p=0.016; figure 1 ). When based on ΔCRP responses were 50% and 39% versus 45% and 56% (p=0.226). Conclusions: In MTX-IR patients, an improvement in the MBDA scores by >22 predicts better response to subsequent Triple Therapy, and lack thereof predicts a better response to anti-TNF. The same analyses using CRP did not reveal similar results. Thus, monitoring patients during MTX treatment using the MBDA score may guide optimal therapy choice in MTX-IRs on the individual patient level. References: Hambardzumyan K, Bolce R, Saevarsdottir S, et al. FRI0005 In Early RA Patients with Non-Response to Methotrexate Monotherapy the Change in Multi-Biomarker Disease Activity Score is Differentially Associated with Subsequent Response to Non-Biological versus Biological Therapy. Annals of the rheumatic diseases. 2014 June 1, 2014;73(Suppl 2):382-3. van Vollenhoven RF, Geborek P, Forslind K, et al. Conventional combination treatment versus biological treatment in methotrexate-refractory early rheumatoid arthritis: 2 year follow-up of the randomised, non-blinded, parallel-group Swefot trial. Lancet. 2012 May 5;379(9827):1712-20. PubMed PMID: 22464340. Centola M, Cavet G, Shen Y, et al. Development of a multi-biomarker disease activity test for rheumatoid arthritis. PloS one. 2013;8(4):e60635. PubMed PMID: 23585841. Pubmed Central PMCID: 3621826. Disclosure of Interest: K. Hambardzumyan: None declared, R. Bolce Shareholder of: Myriad Genetics Inc., Employee of: Crescendo Bioscience, a wholly owned subsidiary of Myriad Genetics, Inc., S. Saevarsdottir: None declared, K. Forslind: None declared, J. Karlsson: None declared, E. Sasso Shareholder of: Myriad Genetics Inc., Employee of: Crescendo Bioscience, a wholly owned subsidiary of Myriad Genetics, Inc., D. Chernoff Consultant for: Crescendo Bioscience, a wholly owned subsidiary of Myriad Genetics, Inc., C. C. Hwang Shareholder of: Myriad Genetics Inc., Employee of: Crescendo Bioscience, a wholly owned subsidiary of Myriad Genetics, Inc., R. van Vollenhoven Grant/research support from: Abb Vie, BMS, GSK, Pfizer, Roch, UCB, Consultant for: Abb Vie, Biotest, BMS, Crescendo Bioscience, GSK, Janssen, Lilly, Merck, Pfizer, Roch, UCB, Vertex